Probability Weighting and Employee Stock Options - Spalt, Oliver G. (Journal of Financial and Quantitative Analysis, 2013)
Abstract This paper documents that riskier firms with higher idiosyncratic volatility grant more stock options to nonexecutive employees. Standard models in the literature cannot easily explain this pattern; a model in which a risk-neutral firm and an employee with prospect theory preferences bargain over the employee's pay package can. The key feature which makes stock options attractive is probability weighting. The model fits the data on option grants well when calibrated using standard parameters from the experimental literature. The results are the first evidence that risky firms can profitably use stock options to cater to an employee demand for long-shot bets.